Knowledge and practice regarding medication use among elderly with chronic diseases in Felda Tembangau 2, Kemayan, Pahang - Farid, Aina Natasha Mohd (Universiti Sains Malaysia, 2024)
The elderly population, defined as those aged 60 and above, faces unique challenges in managing chronic diseases due to physiological changes, limited access to healthcare information, and barriers in understanding and adhering to medication regimens. The aim of this study was to determine the levels of knowledge and practice regarding medication use among elderly with chronic diseases in FELDA Tembangau 2, Kemayan, Pahang and to explore the correlation between these two variables. A cross sectional study was undertaken involving 94 elderly individuals with chronic diseases using purposive sampling. Data on their socio-demographic characteristics, levels of knowledge, and practices regarding medication use were collected through face to face and structured interviews. The findings revealed that the majority of respondents exhibited excellent knowledge (94.7%) and excellent practice (94.7%) regarding medication use. Additionally, a significant positive correlation (r = 0.47, p ≤ 0.01) was found between knowledge and practice levels, indicating that higher knowledge is associated with better practices in medication management. In conclusion, this study might help contribute better understanding of knowledge and practice regarding medication use. However, future research should be done at a different institution with a larger sample size to have generalized results.